1991
DOI: 10.1084/jem.173.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of lck gene expression in T lymphocytes.

Abstract: Summary'Abbreviation used in this paper. UTR, untranslated region . In the mouse and human, mRNA transcripts encoding the lymphocyte-specific protein tyrosine kinase p56ikk are derived from two separate promoters resulting in heterogeneity in the 5' untranslated region sequence. The proximal promoter lies just 5' to the coding region for the gene and is active only in thymocytes . In contrast, the distal promoter lies 34 kilobases (kb) 5' in the human, and is active both in thymocytes and mature peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 41 publications
7
86
3
Order By: Relevance
“…The high p35 expression levels in lck-p35 transgenic thymocytes do not persist in peripheral lymphoid tissues (data not shown), which is in accord with the known down-regulation of endogenous lck proximal promoter activity in mature T cells (32). Analysis of freshly isolated tissues showed that thymus, spleen, and lymph nodes of lck-p35 transgenic mice were indistinguishable from normal control mice.…”
Section: Generation Of Transgenic Mice Expressing the Caspase Inhibitsupporting
confidence: 66%
“…The high p35 expression levels in lck-p35 transgenic thymocytes do not persist in peripheral lymphoid tissues (data not shown), which is in accord with the known down-regulation of endogenous lck proximal promoter activity in mature T cells (32). Analysis of freshly isolated tissues showed that thymus, spleen, and lymph nodes of lck-p35 transgenic mice were indistinguishable from normal control mice.…”
Section: Generation Of Transgenic Mice Expressing the Caspase Inhibitsupporting
confidence: 66%
“…As described previ-ously, exons 16 and 17 of the IRE1␣ gene are floxed in these mice, resulting in a truncated, inactive form of IRE1␣ protein (15). The Cre DNA recombinase is mediated by the Lck promoter, which drives gene expression during thymic development, and the gene is specific for T cells, allowing for a targeted deletion of IRE1␣ gene during T cell development (23,24). Immunoblotting analysis detected the mutant form of IRE1␣ protein in naïve T cells from the IRE1␣ f/f Lck-Cre ϩ mice ( Fig.…”
Section: Ire1␣ Is Required For Optimal Il-4 Production By Cd4mentioning
confidence: 99%
“…In these constructs^ Tpl-2 was placed under the control of the proximal Lck promoter and was expressed specifically in thymocytes (Abraham et al 1991a,b;Wildin et al 1991). Forty-eight transgenic founders, 24 with the wild-type and 24 with the truncated construct, were established.…”
Section: R^mentioning
confidence: 99%
“…Tpl-2 cDNAs containing exon IB were placed under the control of the proximal Lck promoter that is specifically active in thymocytes (Abraham et al 199la,b;Wildin et al 1991). An SV40 large T antigen polyadenylation signal was inserted 3' of the TpI-2 cDNA to ensure proper termination of transcription.…”
Section: Transgenic Constructs Microinjection and Southern Blottingmentioning
confidence: 99%